The Value of Weather Event Science for Pending Climate Policy Decisions. Issue 3 (2nd September 2017) - Donhauser, Justin
Abstract: This essay furthers debate about the burgeoning science of Probabilistic Event Attribution (PEA) and its relevance to imminent climate policy decisions. It critically examines Allen Thompson and Friederike Otto's recent arguments concerning the implications of PEA studies for how the United Nations Framework Convention on Climate Change (UNFCCC) policy framework should be revised during the 2016 'review and decision'. I show that their contention that PEA studies cannot usefully inform decision-making about adaptation policies and strategies is misguided and argue that the current UNFCCC treaty, the 'Paris Agreement', supersedes their proposed revision.